LITERATURE REVIEW: GAMBARAN PENGETAHUAN REMAJA MENGENAI BAHAYA MEROKOK - Atika Nurul Dwi Puteri; Sulastri; Violin Ananta Sonata; Wahyudi (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Adolescence is an important stage in physical, mental, and intellectual development, with an age range of 12–18 years according to WHO. Despite various health campaigns carried out by the government and health organizations, smoking habits among adolescents continue to show an increasing trend. Cigarette smoke has harmful effects on all age groups, from infants to the elderly, including health risks such as low birth weight, respiratory infections, heart disease, and hypertension. A study by Lentera Anak and U-Report UNICEF in 2022 found that the majority of passive smokers were reluctant to remind active smokers to stop, even though they were aware of the dangers. These findings highlight the importance of increasing awareness and interventions to reduce exposure to cigarette smoke and improve adolescent health. This study aims to assess the extent of adolescents’ knowledge regarding the negative impacts of smoking. The method used is a literature review with a narrative approach, exploring research conducted in Indonesia that contains information on the “Description of Adolescent Knowledge about the Dangers of Smoking.”